2008
DOI: 10.1590/s0103-84782009005000082
|View full text |Cite
|
Sign up to set email alerts
|

Germinação in vitro de pólen de híbridos interespecíficos entre o caiaué e o dendezeiro

Abstract: Germinação in vitro de pólen de híbridos interespecíficos entre o caiaué e o dendezeiroIn vitro pollen germination of interespecifics hybrids between caiaué and oil palm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
7
0
2
Order By: Relevance
“…However, E. oleifera is fairly indicated and utilized in species-improvement programs because, despite geographically distant in origin, these two species are compatible in crossbreeding and generate fertile hybrids (Chia et al, 2009). Extensive germplasm collections of the American oil palm (E. oleifera) were made throughout the Amazon River Basin by the Brazilian agricultural research agency Embrapa (Empresa Brasileira de Pesquisa Agropecuária) and the IRHO (Institut de Recherches pour les Huiles et Oleagineux, France) in the mid-1980s, becoming an invaluable source of genetic material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, E. oleifera is fairly indicated and utilized in species-improvement programs because, despite geographically distant in origin, these two species are compatible in crossbreeding and generate fertile hybrids (Chia et al, 2009). Extensive germplasm collections of the American oil palm (E. oleifera) were made throughout the Amazon River Basin by the Brazilian agricultural research agency Embrapa (Empresa Brasileira de Pesquisa Agropecuária) and the IRHO (Institut de Recherches pour les Huiles et Oleagineux, France) in the mid-1980s, becoming an invaluable source of genetic material.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, genetic improvement programs for African oil palm (Elaeis guineenis) have sought the introgression of genes of interest present in germplasm from the American oil palm (Elaeis oleifera). Thus, elite plants of E. guineensis and E. oleifera have been crossed in order to obtain F1 hybrids with good productivity, shorter stature and resistance to disease (Barcelos et al, 2002;Chia et al, 2009;Scherwinski-Pereira et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Chia et al . (), dealing with interspecific hybridization between Elaeis oleifera (Kunth) Cortés and E. guineensis , found lower pollen germination rates. Perhaps this result is due to the long periods of pollen desiccation used by these authors (24 h) instead of 4 h used in our treatments.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that low pollen viability in hybrids of E. guineensis reduces fruit production (Chia et al ., ; Moura et al ., ). The present experiment was aimed at establishing a protocol for evaluating culture media for pollen germination in E. guineensis for use in breeding programmes for this species.…”
Section: Introductionmentioning
confidence: 99%
“…A arquitetura das inflorescências ginandromorfas assemelha-se às inflorescências masculinas normais, apresentando espiguetas cilíndricas elipsoides carregando muitas flores, mas em vez das flores masculinas, desenvolvem-se pequenas flores femininas e a inflorescência é incapaz de produzir pólen (BAUDOUIN, 1983). Além disso, a polinização no HIE é afetada pela baixa atratividade dos polinizadores da espécie africana pelas inflorescências do HIE e pela menor viabilidade de pólen produzido (CHIA et al, 2009). Em virtude dessas características, plantios comerciais de HIE requerem polinização assistida para atingir seu potencial produtivo (CUNHA; LOPES, 2010), o que eleva o custo de produção, pois é necessário produzir ou comprar pólen, e manter rondas para polinização a cada dois ou três dias, para identificar e polinizar inflorescências femininas no período adequado de recepção do pólen.…”
Section: Introductionunclassified